Rational curves on Calabi–Yau threefolds: Verifying mirror symmetry predictions. (September 2016) - Hiep, Dang Tuan
Abstract: In this paper, the numbers of rational curves on general complete intersection Calabi–Yau threefolds in complex projective spaces are computed up to degree six. The results are all in agreement with the predictions made from mirror symmetry.